If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -1c) * 2 = 4(1 + c + 2) Reorder the terms for easier multiplication: 2(1 + -1c) = 4(1 + c + 2) (1 * 2 + -1c * 2) = 4(1 + c + 2) (2 + -2c) = 4(1 + c + 2) Reorder the terms: 2 + -2c = 4(1 + 2 + c) Combine like terms: 1 + 2 = 3 2 + -2c = 4(3 + c) 2 + -2c = (3 * 4 + c * 4) 2 + -2c = (12 + 4c) Solving 2 + -2c = 12 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. 2 + -2c + -4c = 12 + 4c + -4c Combine like terms: -2c + -4c = -6c 2 + -6c = 12 + 4c + -4c Combine like terms: 4c + -4c = 0 2 + -6c = 12 + 0 2 + -6c = 12 Add '-2' to each side of the equation. 2 + -2 + -6c = 12 + -2 Combine like terms: 2 + -2 = 0 0 + -6c = 12 + -2 -6c = 12 + -2 Combine like terms: 12 + -2 = 10 -6c = 10 Divide each side by '-6'. c = -1.666666667 Simplifying c = -1.666666667
| .5(x+4)=.33(3x-6) | | r-6=-6 | | 3x^2-49+200=0 | | 7x-2y+8x+y= | | 4x^4-9x^2+7x+7=0 | | e-10=-3 | | u+6=9 | | 2*3-3+3*4= | | [12-(10-15)]-[6-(7-6)]= | | (p-1)(2p+4)=9 | | 98s^2+648s-5880=0 | | 2s^2+98s-120=0 | | 12d=6+54d | | 98s^2+648s-5881=0 | | 2x+6y=-1 | | x^2+8x+4=9 | | -16n+4=-12n-16 | | y=20+-3x | | 4(7c-1)-2=26c+4 | | 2x^2-9=1 | | 6y-2(y-2)+5= | | 5e+12= | | 4x-4b+x^2b-x^3=0 | | (x+3)=(3x-91) | | (2x+1)=(3x-4) | | ax-bx-a^2+b^2=2a-2b | | ax-bx-a^2+b^2=2ab-2b | | (2x+15)=(6x-57) | | x^7=16870 | | x-2=.5x+5 | | 9y^3-7=y-63y^2 | | .75x-.25x+5=27 |